MUSICAL EXPRESSION IN ART PERFORMANCE THROUGH YOUTUBE MEDIA IN THE PANDEMI COVID-19 - DANI NUR SAPUTRA (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
Recently the covid pandemi virus 19 phenomena occurred in various countries, including Indonesia. This phenomenon has an impact on the limitation of space for artists in expression. Therefore, artists look for other alternatives as a medium of performance art. For example, artists find stage shows through YouTube. Youtube is one of the media to channel and display their work so that many people can watch it. This research uses a descriptive qualitative method and uses a case study approach. Data collection techniques used in this study are observations and interviews with semi-structured techniques. The study results explain that musikal expression in the performing arts through YouTube is an important aspect to attract the audience's attention and get the number of likes and subscribes. The difference in artists' musikal expressions when they perform on youtube compared to being directly seen is more pronounced, mainly when artists are shot closely. In addition, this study shows that youtube media provides an alternative for artists to display their work without the limitation of space for expression and creation.